2018
DOI: 10.1177/1945892418801083
|View full text |Cite
|
Sign up to set email alerts
|

Role of Superantigens in Allergic Inflammation: Their Relationship to Allergic Rhinitis, Chronic Rhinosinusitis, Asthma, and Atopic Dermatitis

Abstract: Objectives Our intention was to review all material published to date regarding superantigens (SAgs) and allergy from an otorhinolaryngological viewpoint to understand this association more clearly. Methods We identified all materials published mentioning both SAg and allergic rhinitis (AR), chronic sinusitis, asthma, and atopic dermatitis (AD) that are indexed on PubMed, Google, or the ProQuest Central databases. Results Staphylococcus aureus is a significant bacterial pathogen in humans and has the ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 127 publications
1
22
0
Order By: Relevance
“…A number of studies have found a higher abundance of Staphylococcal bacteria in the upper respiratory tract of patients with chronic rhinosinusitis 66,67 and a reduction in diversity 68 . Staphylococcus has also been found positively associated with other respiratory diseases, such as allergic rhinitis and asthma 69 . While other factors could be playing a role in the upper respiratory symptoms experienced by the crew at the ISS, an elevated relative abundance of nasal Staphylococcal bacteria is consistent with these symptoms 10 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have found a higher abundance of Staphylococcal bacteria in the upper respiratory tract of patients with chronic rhinosinusitis 66,67 and a reduction in diversity 68 . Staphylococcus has also been found positively associated with other respiratory diseases, such as allergic rhinitis and asthma 69 . While other factors could be playing a role in the upper respiratory symptoms experienced by the crew at the ISS, an elevated relative abundance of nasal Staphylococcal bacteria is consistent with these symptoms 10 .…”
Section: Discussionmentioning
confidence: 99%
“…[25] Current studies indicate that colonized SSAg-producing S. aureus intensify cutaneous inflammation of atopic dermatitis and Sézary syndrome and promote tumor progression in Sézary syndrome. [26,27] Antibiotics have an ameliorating effect on inflammation in these conditions, [28] [29] Oral antibiotics are also administered as a treatment for LyP. However, because LyP is a chronic condition characterized by intermittent flare ups of lesions, it is difficult to determine the long term effectiveness of anti-Staphylococcal antibiotics for LyP.…”
Section: Discussionmentioning
confidence: 99%
“…6 Further, SAg-Sau colonization has been associated with a range of inflammatory/autoimmune conditions, including asthma, chronic rhinosinusitis, Wegener's granulomatosis (WG) and multiple sclerosis (MS). 3,[7][8][9] Nasopharynx-associated lymphoid tissues (NALT) are mucosal immune organs in the upper respiratory tract and are known induction sites for immunity against a number of respiratory pathogens. The exposure to a large number of microbial antigens results in a substantial number of proinflammatory T cells in NALT which could potentially lead to a highly inflammatory response in the presence of SAg-Sau.…”
Section: Introductionmentioning
confidence: 99%